Preparation method for desulfurization, grafting, modification and regeneration of waste rubber

By using the synergistic effect of desulfurization agent and graft monomer under high temperature and strong shearing, the efficient desulfurization and graft modification treatment of waste rubber is solved, the problems of recycling and recycling of waste rubber are improved, and the processing performance of recycled rubber is achieved, and high-value recycling is achieved.

CN119751765APending Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411894104.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively solve the problems of recycling and recycling of waste rubber, and traditional methods have problems of resource waste and environmental pollution.

Method used

A preparation method for desulfurization and graft modification regeneration of waste rubber is adopted. By using the synergistic effect of desulfurization agent and graft monomer under high temperature and strong shearing, the efficient desulfurization and graft modification treatment of waste rubber is achieved.

Benefits of technology

This method can quickly and large-scale recycling of waste rubber, improve the processing performance of recycled rubber, realize high-value recycling of waste rubber, and solve the problem of excessive accumulation of waste rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751765A_ABST
    Figure CN119751765A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for desulfurization, grafting, modification and regeneration of waste rubber. The high-strength waste rubber is prepared from the following raw materials in parts by mass: 100 parts of waste rubber, 0.1-5 parts of a desulfurizing agent, 0.1-5 parts of a grafting monomer and 5-20 parts of a softening agent. The preparation method comprises the following steps: crushing the waste rubber into small particles in a crusher, uniformly mixing the small particles with the desulfurizing agent, the grafting monomer and the softening agent, and carrying out shearing desulfurization and grafting in thermal mechanical processing equipment to obtain the desulfurized grafted modified waste rubber. According to the invention, the synergistic effect of the desulfurizer and the surface modifier is ingeniously fused, and grafting modification treatment is carried out while the waste rubber is efficiently desulfurized, so that the processability of the reclaimed rubber is ensured to the greatest extent, the recovery effect of the waste rubber is improved, the environmental pollution is reduced, and the resource utilization of the waste is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of waste rubber recycling and reuse, and specifically relates to a preparation method for waste rubber desulfurization grafting modification regeneration. Background Art

[0002] Rubber is an indispensable raw material for modern industry. With the advancement of science and technology and the rapid development of industry, the application scope of rubber is becoming wider and wider, and the consumption is increasing, resulting in a large amount of waste rubber every year. For such a large amount of waste rubber, if it is not handled properly, it will easily cause "black pollution", which will not only cause serious pollution to the environment but also affect human health. Due to its dense three-dimensional network structure, waste rubber is difficult to decompose, making its recycling more difficult. The traditional treatment method is to landfill and incinerate waste rubber, which not only wastes resources, but the decomposition of organic matter also leads to more serious pollution, and is now banned by many countries. In order to respond to the call for green chemistry and environmental protection, scientific researchers continue to improve technology to recycle waste rubber.

[0003] At present, there are two mainstream methods for rubber recycling. One is to crush waste rubber into particles or powders by physical methods. These particles and powders can be used as fillers to reduce production costs, and can also be used as mixed components of rubber matrix and other materials to achieve effective resource recycling and reuse. They are widely used in asphalt roads. However, due to the unique three-dimensional cross-linked network structure of waste rubber powder and the chemical inertness on its surface, it often faces dispersion problems when directly filled into rubber blends, which in turn affects the overall performance of the blends. Rubber powder as filler has a positive effect on the matrix only when used in small amounts. Another recycling method is to accurately destroy the original three-dimensional cross-linked network structure of waste rubber, so that it can be effectively restored to a linear molecular chain form, which is convenient for subsequent reprocessing and finally recycled as high-quality reclaimed rubber. It has a high economic value and is also the mainstream method for recycling waste rubber. At present, the recycling methods that are widely used include mechanical desulfurization, mechanochemical desulfurization, microwave desulfurization, ultrasonic desulfurization, etc. Mechanical chemical desulfurization is a relatively popular method. Under the action of chemical additives, desulfurization regeneration is achieved through high-temperature shearing. This method can be processed quickly, has a large output, and can solve the current problem of large amounts of waste rubber accumulation.

[0004] CN110540675A discloses a method for desulfurization of rubber. In the stirring desulfurization process of waste rubber powder, by adding clean water to the desulfurization tank every 1-3 minutes to keep the waste rubber powder continuously moist, local agglomeration and scorching can be effectively prevented. However, this method makes the production process of rubber desulfurization relatively cumbersome. CN116355278A discloses a method for continuously preparing oil-free high-strength tire regenerated rubber. This method can continuously desulfurize production and significantly improve production efficiency. This method can only achieve partial desulfurization of rubber, and the undesulfurized part still presents inertia and has no processing performance, which has a certain negative impact on its regeneration effect. In this regard, in order to realize the recycling of waste rubber, a preparation method for desulfurization grafting modification and regeneration of waste rubber is proposed. Grafting is performed while desulfurizing the waste rubber to maximize the performance of the regenerated rubber. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method for desulfurization grafting modification regeneration of waste rubber, which cleverly integrates the synergistic effect of a desulfurizer and a surface modifier, and performs grafting modification treatment while efficiently desulfurizing the waste rubber, thereby ensuring the processing performance of the reclaimed rubber to the greatest extent and realizing high-value recovery of the waste rubber.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is a preparation method for desulfurization grafting modification and regeneration of waste rubber, and the formula is as follows (by mass fraction):

[0007]

[0008] The waste rubber is crushed in a crusher to obtain small pieces of waste rubber. The raw materials are mixed evenly according to the above formula, and the blend is placed in a thermal mechanical processing equipment for desulfurization grafting modification and regeneration.

[0009] Furthermore, the waste rubber is formed by sulfur vulcanization.

[0010] Furthermore, the desulfurizing agent is one or more of zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate and diphenyl disulfide.

[0011] Furthermore, the grafting monomer is one or more of maleic anhydride, itaconic acid, acrylic acid, methacrylic acid and glycidyl methacrylate.

[0012] Furthermore, the softener is one or more of paraffin oil, aromatic oil and petroleum resin.

[0013] Furthermore, the thermomechanical processing equipment is one or a combination of an open mixer, an internal mixer, a single-screw extruder, a twin-screw extruder and a triple-screw extruder.

[0014] Furthermore, the processing regeneration temperature of the thermomechanical processing equipment is 100°C-250°C, preferably 170-185°C.

[0015] Furthermore, the processing speed of the thermal mechanical processing equipment is 50-550r / min.

[0016] In the preparation method of the present invention, when the waste rubber is desulfurized under high temperature and strong shearing action, free radical collision grafting reaction occurs simultaneously.

[0017] Compared with the existing technology, the present invention has the following advantages:

[0018] (1) The present invention uses a one-pot method to combine waste rubber, a desulfurizing agent, a softener, and a grafting monomer to achieve desulfurization and grafting modification of waste rubber. The process flow is simple, the processing operation is concise, and waste rubber can be quickly and massively recovered, thereby solving the current problem of excessive accumulation of waste rubber.

[0019] (2) The present invention ingeniously combines the synergistic effect of the desulfurizer and the grafting monomer to efficiently desulfurize the waste rubber while performing grafting modification treatment, thereby ensuring the processing performance of the reclaimed rubber to the greatest extent and achieving high-value recovery of the waste rubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the thermogravimetric composition analysis of the waste EPDM rubber strips in Examples 1-4 and Comparative Examples 1-3.

[0021] Figure 2 This is an example diagram of the endpoint of titration using the equilibrium titration method in Example 2.

[0022] Figure 3a and Figure 3b The sol of Example 2, Comparative Example 2 and Comparative Example 3 1 HNMR spectrum.

[0023] Figure 4 It is the infrared image of the gel of Example 2 and Comparative Example 2.

[0024] Figure 5 The Mooney viscosity test of Examples 1-4, Comparative Example 2 and Comparative Example 3 is shown.

[0025] Figure 6 It is the sol content of the modified waste rubber in Examples 5-9 as the temperature changes.

[0026] Figure 7 It is the grafting rate of the modified waste rubber in Examples 5-9 as the temperature changes.

[0027] Figure 8 It is a diagram showing the chain breakage of rubber regenerated by different devulcanizing agents in Comparative Example 3, Example 2, Example 10 and Example 11.

[0028] Fig. 9 This is a real picture of the extrusion of Example 4. DETAILED DESCRIPTION

[0029] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Examples 1-4

[0031] This embodiment provides a preparation method for desulfurization grafting modification and regeneration of waste rubber, and the preparation steps are as follows:

[0032] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder, and the mixture is stirred and mixed according to the formula described in Table 1. The obtained mixture is added to a twin-screw extruder, and desulfurized and grafted at a shear temperature of 180° C. and 130 r / min. The material is discharged and granulated to obtain desulfurized and grafted modified waste rubber;

[0033] Example 5

[0034] The pure EPDM vulcanized rubber was crushed into small particles by a pelletizer, and 100 parts of pure EPDM vulcanized rubber, 1 part of desulfurizing agent zinc diethyldithiocarbamate, 1 part of grafting monomer maleic anhydride, and 5 parts of softening agent paraffin oil were stirred and mixed, and shear modified by a torque rheometer at 170°C and 60r / min to obtain desulfurized grafted modified waste rubber.

[0035] Example 6

[0036] The pure EPDM vulcanized rubber was crushed into small particles by a pelletizer, and 100 parts of pure EPDM vulcanized rubber, 1 part of desulfurizing agent zinc diethyldithiocarbamate, 1 part of grafting monomer maleic anhydride, and 5 parts of softening agent paraffin oil were stirred and mixed, and shear modified by a torque rheometer at 180°C and 60r / min to obtain desulfurized grafted modified waste rubber.

[0037] Example 7

[0038] The pure EPDM vulcanized rubber was crushed into small particles by a pelletizer, and 100 parts of pure EPDM vulcanized rubber, 1 part of desulfurizing agent zinc diethyldithiocarbamate, 1 part of grafting monomer maleic anhydride, and 5 parts of softening agent paraffin oil were stirred and mixed, and shear modified by a torque rheometer at 190°C and 60r / min to obtain desulfurized grafted modified waste rubber.

[0039] Example 8

[0040] The pure EPDM vulcanized rubber was crushed into small particles by a pelletizer, and 100 parts of pure EPDM vulcanized rubber, 1 part of desulfurizing agent zinc diethyldithiocarbamate, 1 part of grafting monomer maleic anhydride, and 5 parts of softening agent paraffin oil were stirred and mixed, and shear modified by a torque rheometer at 200°C and 60r / min to obtain desulfurized grafted modified waste rubber.

[0041] Example 9

[0042] The pure EPDM vulcanized rubber was crushed into small particles by a pelletizer, and 100 parts of pure EPDM vulcanized rubber, 1 part of desulfurizing agent zinc diethyldithiocarbamate, 1 part of grafting monomer maleic anhydride, and 5 parts of softening agent paraffin oil were stirred and mixed, and shear modified by a torque rheometer at 210°C and 60r / min to obtain desulfurized grafted modified waste rubber.

[0043] Example 10

[0044] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM, 1 part of desulfurizer zinc dimethyldithiocarbamate, 5 parts of softener paraffin oil, and 1 part of grafting monomer maleic anhydride are stirred and mixed. The resulting mixture is added to a twin-screw extruder and modified at a shear temperature of 180°C and 130r / min to obtain modified waste rubber.

[0045] Embodiment 11

[0046] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM, 1 part of desulfurizer diphenyl disulfide, 5 parts of softener paraffin oil, and 1 part of grafting monomer maleic anhydride are stirred and mixed. The resulting mixture is added to a twin-screw extruder and modified at a shear temperature of 180°C and 130r / min to obtain modified waste rubber.

[0047] Example 12

[0048] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM, 1 part of desulfurizer zinc diethyldithiocarbamate, and 5 parts of softener aromatic oil are stirred and mixed. The resulting mixture is added to a twin-screw extruder and modified at a shear temperature of 180°C and 130r / min to obtain modified waste rubber.

[0049] Example 13

[0050] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM, 1 part of desulfurizer zinc diethyldithiocarbamate, and 5 parts of softener petroleum resin are stirred and mixed. The resulting mixture is added to a twin-screw extruder and modified at a shear temperature of 180°C and 130r / min to obtain modified waste rubber.

[0051] Comparative Example 1

[0052] The waste EPDM rubber strips are broken into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM and 5 parts of softener paraffin oil are stirred and mixed. The resulting mixture is added to a twin-screw extruder and mechanically modified at a shear temperature of 180°C and a speed of 130 r / min. The material is discharged and granulated to obtain mechanically modified waste rubber.

[0053] Comparative Example 2

[0054] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM, 1 part of desulfurizer zinc diethyldithiocarbamate, and 5 parts of softener paraffin oil are stirred and mixed. The resulting mixture is added to a twin-screw extruder and desulfurized and modified at a shear temperature of 180°C and a speed of 130r / min. The material is discharged and granulated to obtain desulfurized and modified waste rubber.

[0055] Comparative Example 3

[0056] The waste EPDM rubber strips are broken into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM, 1 part of grafted monomer maleic anhydride, and 5 parts of softener paraffin oil are stirred and mixed. The resulting mixture is added to a twin-screw extruder and grafted and modified at a shear temperature of 180°C and a speed of 130r / min. The material is discharged and granulated to obtain grafted modified waste rubber.

[0057] Comparative Example 4

[0058] The waste EPDM rubber strips are crushed into small particles by a pelletizer so that they can be added to the feed port of a twin-screw extruder. 100 parts of waste EPDM and 1 part of a desulfurizing agent, zinc diethyldithiocarbamate, are stirred and mixed. The resulting mixture is added to a twin-screw extruder and modified at a shear temperature of 180°C and a speed of 130 r / min to obtain modified waste rubber.

[0059] Table 1 Desulfurization grafting modification formula of different parts of grafted monomer

[0060]

[0061] Note: The desulfurizer is zinc diethyldithiocarbamate, the grafting monomer is maleic anhydride, and the softener is paraffin oil.

[0062] The materials in the above embodiments and comparative examples were tested, and the test results are as follows:

[0063] 1. Calculation method of sol content: Wrap the sample with filter paper and put it into Soxhlet extractor, filter with acetone for 10 hours to remove unreacted substances and small molecules, dry and weigh, record as m1, extract with dichloromethane for 72 hours, the cross-linked rubber will be extracted, and the residue with cross-linked structure will be retained in the filter paper, dry and weigh, record as m2. Calculate the sol content according to the following formula:

[0064]

[0065] Where m1 is the mass of the sample before extraction, m2 is the mass of the sample after extraction, and w is the mass fraction of rubber in the sample.

[0066] 2. Calculation of cross-link density: Use the equilibrium swelling method to measure the cross-link density of the extracted gel. Take a certain mass mr of gel and soak it completely in the solvent xylene for 72 hours at room temperature. Take out the swollen gel, quickly wipe off the solvent on the surface of the gel with filter paper, put it on the balance and weigh it, recorded as m2. ms is m2 minus mr. Use the Flory-Rehner equation to calculate the cross-link density of the gel:

[0067]

[0068]

[0069] Where Ve represents the crosslinking density of the rubber (mol / cm 3 ), Vr represents the volume fraction of rubber in the material after swelling, χ represents the interaction parameter between rubber and solvent (χ takes the empirical value of 0.43), and Vs represents the molar volume of the solvent (xylene is 121.9 cm 3 / mol), ρr represents the density of rubber (1.143 g / cm 3 ), ρs represents the density of the solvent used in the test (xylene is 0.9 g / cm 3 ).

[0070] 3. Titration standard solution: 0.05mol / L KOH ethanol solution, phenolphthalein as indicator. Take 0.5g of purified and dried sol, dissolve it in 50ml xylene, and after it is completely dissolved, add 0.05mol / L KOH ethanol solution, phenolphthalein as indicator, and shake while dropping. When the solution turns pink, it is the titration end point. At the same time, make a blank control group.

[0071]

[0072] C: 0.05 mol / L KOH ethanol solution, V1: volume consumed by the sample, V2: volume consumed by the blank sample, m: mass of the sol.

[0073] 4. Use AVANCE III HD 600 spectrometer to test the 1H-NMR of the sample, extract and dissolve with dichloromethane, wash with ethanol several times to obtain a pure sol, and perform 1H-NMR analysis on the de-crosslinked sol components. The solvent is deuterated chloroform (CDCl3), the concentration is about 150 mg / mL, and the test frequency is 600 MHz.

[0074] 5. After complete extraction in dichloromethane solution (about 72 hours), the remaining gel part was subjected to Fourier transform infrared attenuated total reflectance test (FTIR-ATR) in the test range of 4000~650cm -1 , the number of scans is 32 times.

[0075] 6. According to the national standard GB / T1232.1-2000, the Mooney viscosity of the sample was measured at 100°C.

[0076] Table 2 Test results of sol content, crosslinking density, decreased crosslinking density and grafting rate of Examples 1-4 and Comparative Examples 1-3

[0077]

[0078]

[0079] The crosslink density of the undesulfurized rubber is 9.02 x 10 -4 mol / cm -3

[0080] The degree of desulfurization of rubber can be expressed by sol content and crosslinking density. As can be seen from Table 2, in Comparative Example 1, no desulfurizer and grafting monomer were added, and its sol content was low and the crosslinking density was high, which shows that the desulfurization effect of simple mechanical shearing was poor; in Comparative Example 3, after adding MAH grafting, the sol content increased slightly and the crosslinking density decreased slightly. This is because MAH reacts with the active free radicals generated by the broken chain to prevent it from crosslinking again, so its desulfurization effect is better than that of Comparative Example 1. After adding the desulfurizer, Examples 1-4 can quickly react with the crosslinking bonds of the waste rubber for desulfurization, the sol content increases, the crosslinking density decreases significantly, and has a better desulfurization effect. The sol content of Example 2 is 31.83%, and the lowest crosslinking density is 1.81x10 -4 mol / cm 3When different amounts of MAH were used for the test in Examples 1-4, the sol content and crosslinking density of the waste rubber did not show significant differences, which indicates that grafting has little effect on the desulfurization effect during desulfurization, and grafting can introduce new groups to provide activity to the waste rubber and expand its application. Moreover, with the increase of the amount of MAH, the grafting rate of the modified waste rubber first increased significantly and then tended to stabilize. The highest grafting rate (0.232%) was reached when the amount of MAH was 1phr.

[0081] like Figure 3a and Figure 3b As shown 1 HNMR test, in the comparative analysis of the three sample sols of Comparative Example 2, Comparative Example 3 and Example 2 1 When looking at the HNMR graph, we observed that at chemical shifts of 2.73ppm and 6.35ppm, significant new peaks appeared in the sample of Example 2 compared to the sample of Comparative Example 2. Specifically, the peak at 2.73ppm may be attributed to the methylene hydrogen atom connected to the carbon group in the maleic anhydride molecule, while the peak at 6.35ppm may correspond to the σ hydrogen atom on the carbon group of maleic anhydride. This finding is consistent with the description in the literature that the double bond of maleic anhydride is opened and successfully grafted onto the rubber molecule, thus confirming that maleic anhydride has been successfully grafted onto the surface of the waste rubber sol. Figure 4 The infrared images of the gels of Example 2 and Comparative Example 2 show that the infrared images of Example 2 at 1784 and 1850 cm -1 The characteristic peaks of maleic anhydride appeared in other places, which shows that the desulfurization grafting modification has the effect of grafting modification on the entire surface of the waste rubber, which greatly improves the surface inertness of the waste rubber, thereby improving its reprocessing performance.

[0082] Figure 5 The Mooney viscosity of the modified waste rubber was tested by a Mooney viscometer to determine the processing fluidity of the modified waste rubber. In Comparative Example 3, when no desulfurizer was added for modification, the desulfurization degree was low, the waste rubber still remained chemically inert, and its Mooney viscosity was large, making it difficult to process and shape; in Examples 1-4, after desulfurization with the addition of a desulfurizer, the Mooney viscosity dropped sharply, and the waste rubber had good processing fluidity at this time. The Mooney viscosity increased with the increase in the amount of maleic anhydride, but the amplitude was not large, and the waste rubber still maintained good processing performance. In addition, maleic anhydride also introduced new groups, which was conducive to improving its regeneration performance.

[0083] like Figure 6 , 7 As shown, Examples 5-9 use pure EPDM vulcanizate to study the effect of temperature change on its desulfurization grafting in a torque rheometer. Figure 6 It can be seen that with the increase of temperature, the sol content increases, indicating that its cross-linking network is more open and the desulfurization degree is better; Figure 7As the temperature increases, the grafting rate first increases and then decreases. The reason why the grafting rate increases at the beginning is that the free radical reaction is promoted under the action of thermal shear, so the grafting rate increases. The temperature continues to increase and reaches the boiling point of the grafting monomer maleic anhydride, which causes it to volatilize without reacting, and the grafting rate decreases. Therefore, in the preparation of desulfurized grafted modified waste rubber, it is necessary to comprehensively consider the two aspects of desulfurization and grafting in order to obtain desulfurized grafted modified waste rubber with better performance.

[0084] Figure 8 This is a diagram of the chain breaking of rubber regenerated by different desulfurization agents in Example 3, Example 2, Example 10 and Example 11. When the waste rubber is processed and desulfurized, the main chain and cross-linking bonds will generally break. In order to ensure the performance of the regenerated rubber, we hope that the rubber can be mainly cross-linked. The fracture situation can be analyzed according to the Horikx theory. Figure 8 There are two curves in the figure, which are fitted according to the Horikx theory. The black solid line indicates that only the main chain breaks during the regeneration process; the red dotted line indicates that only the cross-linking bond breaks during the regeneration process. As shown in the figure, in Comparative Example 3, no desulfurizer is added, and the main chain breaks mainly occur, which seriously affects the performance of rubber regeneration. After adding the desulfurizer, Examples 2, 10 and 11 both the main chain breaks and the cross-linking bond breaks occur, which shows that adding a desulfurizer can have a positive effect on the rubber recycling performance.

[0085] Table 3 is the test results of sol content and crosslinking density of Comparative Example 2, Comparative Example 4, Example 12 and Example 13.

[0086] sample Sol content (%) <![CDATA[Crosslink density (10 -4 mol / cm 3 )]]> Comparative Example 4 25.52 2.68 Comparative Example 2 31.1 1.94 Example 12 30.8 1.87 Example 13 30.8 1.85

[0087] Fig. 9 As shown, the modified sample obtained by extruding without adding a softener in Comparative Example 4 is difficult to form, and it can be seen from Table 3 that the sol content of Comparative Example 4 is low, the crosslinking density is large, and the desulfurization effect is poor. Without adding a softener, the rubber molecular chain shrinks more tightly, and it is difficult for the mechanical thermal shear to bring the desulfurizer into the rubber, resulting in a poor desulfurization effect. After adding a softener, the viscosity of the rubber is reduced, the processing difficulty is reduced, and the recycling effect is better.

[0088] From the above test results, we can see that we have successfully prepared desulfurized grafted modified waste rubber. This recycling method cleverly combines the synergistic effect of desulfurizer and surface modifier. While efficiently desulfurizing the waste rubber, it also performs grafting modification, which guarantees the processing performance of the reclaimed rubber to the greatest extent. This innovative process has greatly improved processing efficiency and output, and provides a rapid and effective solution to the severe challenge of the current accumulation of waste rubber resources.

[0089] The present invention is described in detail above in conjunction with the embodiments. It should be noted that the various specific technical features described in the above specific embodiments can be combined and changed in any suitable manner without contradiction, and the present invention will not further describe various possible combinations. In addition, other variations and combinations of the various technical features of the present invention should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A preparation method for desulfurization grafting modification and regeneration of waste rubber, the formula is calculated by mass as follows: The waste rubber is crushed in a crusher to obtain small pieces of waste rubber. The raw materials are mixed evenly according to the above formula, and the blend is placed in a thermal mechanical processing equipment for desulfurization grafting modification and regeneration.

2. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The waste rubber is formed by sulfur vulcanization.

3. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The desulfurizing agent is one or more of zinc dimethyl dithiocarbamate, zinc diethyl dithiocarbamate and diphenyl disulfide.

4. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The grafting monomer is one or more of maleic anhydride, itaconic acid, acrylic acid, methacrylic acid and glycidyl methacrylate.

5. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The softener is one or more of paraffin oil, aromatic oil and petroleum resin.

6. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The thermomechanical processing equipment is one or a combination of open mixer, internal mixer, single screw extruder, twin screw extruder and triple screw extruder.

7. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The processing and regeneration temperature of the thermomechanical processing equipment is 100℃-250℃.

8. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The processing and regeneration temperature of thermomechanical processing equipment is 170-185℃.

9. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: The processing and regeneration speed of the thermomechanical processing equipment is 50-550r / min.

10. The method for preparing waste rubber by desulfurization grafting modification and regeneration according to claim 1, characterized in that: Under high temperature and strong shearing action, when the waste rubber is devulcanized, free radical collision grafting reaction occurs simultaneously.

Citation Information

Patent Citations

  • Method for desulfurizing rubber

    CN110540675A

  • Method for continuously preparing oil-free high-strength tire reversion regenerated rubber

    CN116355278A

  • Flame-retardant smoke-suppression non-cured rubber asphalt waterproof coating capable of being constructed at normal temperature

    CN111117487A

  • Functionalized reversion liquid rubber and preparation method thereof

    CN114478840A

  • Improvements in and relating to the reclaiming of natural and synthetic rubbers

    EP0690091A1